Analysis of factors contributing to postoperative body weight change in patients with gastric cancer: based on generalized estimation equation - Tian, Qiuju; Qin, Liyuan; Zhu, Weiyi; Xiong, Shaojie; Wu, Beiwen (PeerJ, 2020)
Aims The study aimed to explore factors contributing to body weight change over time in gastric cancer patients after gastrectomy, in order to find risk factors to implement nutritional intervention beforehand. Methods A cohort of gastric cancer patients who were treated with gastrectomy from January to March 2019 at a university affiliated hospital in Shanghai were consecutively identified in this study. Demographics, disease related information, nutrition knowledge, attitude, and practice score were collected before gastrectomy. In addition, body weight before surgery (T0), body weight at one month (T1), two months (T2), and three months (T3) after gastrectomy were recorded. Generalized estimation equation was used to describe body weight change and analyze factors contributing to body weight change after surgery. Results There were 49 patients recruited in the study. Patient body weight decreased by 9.2% at T1 (Wald χ = 271.173, P <0.001), 11.0% at T2 (Wald χ2 = 277.267, P <0.001), and 11.4% at T3 compared to baseline at T0 (Wald χ = 284.076, P <0.001). The results of GEE for multivariable analysis showed that surgery type (Wald χ = 6.027, P = 0.014) and preoperative BMI (Wald χ = 12.662, P = 0.005) were contributing factors of body weight change. Compared with distal gastrectomy patients, total gastrectomy patients experienced greater body weight loss (β = 2.8%, P = 0.014). Compared with patients with BMI&λτ; 18.5 kg/m2, patients with BMI ≥ 25 kg/m2experienced greater body weight loss (β = 4.5% P = 0.026). Conclusion Gastric cancer patients experienced significant weight loss during 3 months after gastrectomy. Total gastrectomy and BMI ≥ 25 kg/m2were risk factors to postoperative body weight loss for GC patients. The results suggested hinted that clinician should pay attention to postoperative nutrition status of patient undergoing total gastrectomy and obesity patients.
Keywords: Gastric cancer; Body weight loss; Gastrectomy; Body mass index